ANALISIS SWOT PADA UMKM BOLA UBI LUMER CRISPY UNTUK MENINGKATKAN STRATEGI DAN DAYA SAING - Nikken Syakira Haq; Tyna Yunita, Arya Bayu Sayeti, Rewang Budi Prasetyo (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
This research was carried out because many MSMEs are similar to the “Bobimercy” business. It is interesting to study because “Bobimercy” the food business from processed sweet potatoes, is a company that is always trying to develop to continue competing with other competitors. This qualitative descriptive study focuses on SWOT analysis to help “Bobimercy” business owners increase competitiveness to compete with similar SMEs. The presence of the culinary business is now the latest trend that makes a person less willing to consume traditional food. The data collection technique used was a literature review and observation study method. The ST strategy, which uses strength factors to overcome threat factors, is a strategy obtained based on the analysis of the SWOT matrix and the IFAS-EFAS matrix. This implementation aims to improve product quality so that it can compete with other cassava processed business products and innovate products with different advantages from the others. Bobimercy stands for crispy melted sweet potato balls. This product was created and launched in March 2023, to be precise. Crispy sweet potato balls are produced hygienically to maintain the quality and image of the product so that it reaches the customer in a clean condition